Paleoecology, Biostratigraphy, Paleoceanography and Taxonomy of Agglutinated Foraminifera 1990
DOI: 10.1007/978-94-011-3350-0_11
|View full text |Cite
|
Sign up to set email alerts
|

Recent Deep-Sea Agglutinated Foraminifera: A Brief Review

Abstract: ABSTRACT.Benthic foraminifera are important members of the deep-sea biota and sometimes are the dominant organisms in the meiofaunal and macrofaunal size ranges and in hard substrate communities. Agglutinated species are abundant and include a rich diversity of undescribed taxa, many of them belonging to soft-bodied groups, e.g. the Komokiacea. These delicate forms are particularly important in tranquil, central oceanic regions below the carbonate compensation depth, where calcareous species are rare. Large ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 85 publications
1
23
0
1
Order By: Relevance
“…Tube-like agglutinated foraminifera that use planktonic foraminifer shells in their construction are common in bathyal and abyssal environments worldwide, where they live either as suspension or deposit feeders (Gooday, 1990). Fragments are difficult to assign to genus level if the proloculus is absent and the branching pattern unclear, as is the case with the pieces described here.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…Tube-like agglutinated foraminifera that use planktonic foraminifer shells in their construction are common in bathyal and abyssal environments worldwide, where they live either as suspension or deposit feeders (Gooday, 1990). Fragments are difficult to assign to genus level if the proloculus is absent and the branching pattern unclear, as is the case with the pieces described here.…”
Section: Introductionmentioning
confidence: 66%
“…2). Although polychaetes, nematodes, and crustaceans are all known to construct agglutinated tubes (Gooday, 1990;Finger et al, 2008), the specimens described here can be securely identified as a foraminifer because of the small size and mode of construction which is similar to other agglutinated foraminifera including Rhizammina from the same sample. As in Rhizammina (see Fig.…”
Section: Descriptionmentioning
confidence: 77%
See 1 more Smart Citation
“…Small, abyssal, thin-walled smooth multichambered morphotypes-infaunal detrital/bacterial scavengers with the ability to survive under extreme oligotrophic conditions by such mechanisms as metabolizing protoplasm during resting phases or bacterial encystment (Gooday, 1990).…”
Section: Distribution Of Faunal Groupsmentioning
confidence: 99%
“…строят стенку из спикул губок Koho, 2008;Maldonado et al, 2013). Также известны случаи ее построения исключительно из кокколитофорид (нижний баррем Восточной Англии (Thomsen, Rasmussen, 2008), маастрихт Центральной Пацифики или раковин планктонных фораминифер (Gooday, Smart, 2000;Maldonado et al, 2013).…”
Section: Introductionunclassified